Genetic Divergence Analysis on some Bread Wheat Genotypes Grown in Ethiopia - Daniel HAILEGIORGIS (Journal of Central European Agriculture, 2011)
An investigation was carried out with 49 bread wheat genotypes to assess the genetic diversity for yield and yield related traits. The Unweighted Pair Group Method using Arithmetic Averages (UPGMA) technique was used for the analysis. The genotypes were evaluated for 17 Characters and showed wide variability for the components studied. The cluster analysis grouped the 49 bread wheat genotypes into 22 different clusters. This indicates the presence of wide diversity among the tested genotypes. From cluster mean values, genotypes in cluster 9 and 13 deserve consideration for their direct use as parents in hybridization programs to develop high yielding wheat varieties. The genotypes in cluster 3 and 16 may be used for improvement of protein and gluten contents, early maturity-ness and other desirable characters other than grain yield. The result of the principal components analysis revealed that nine principal components (PC1 to PC9) accounted nearly 80 % of the total variation. It was also noted that differentiation of genotypes into different clusters was because of the small contribution of few character rather than the cumulative effect of a number of characters. The information obtained from this study can be used to plan crosses and maximize the use of genetic diversity and expression of heterosis.